Migration And Identity : The Iban In Sabah, Malaysia. - Mersat, Neilson Ilan; Sanggin, S.E. (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This paper is based on a study on Iban Diaspora in Borneo carried out by Institute of East Asian Study, Universiti Malaysia Sarawak. The project started in 2009. It examines the history of Iban migration from Sarawak to Sabah in the 1940s. The objectives of the study were to determine the status of the Iban migrants in Tawau and their motives for migration, to determine when and how the migrants ended up in the present locations, to determine how the migrants culturally and economically adapt themselves to the present locations?, to determine the role the migrants played in local politics (i.e. in Sabah) and how the host state’s policies accommodated the “new comers”.